Mechanical Evaluation of Laminates Based on Phenolic Resins using Lignins as Partial Substitutes for Phenol - Taverna, María Eugenia (2015)
Reducing the consumption of phenol during synthesis of phenolic resins is of great technological and scientific interest because of its economic and environmental implications. In this work, the use of hydroxymethylated lignins as a partial replacement for phenol in resol phenol-formaldehyde resins used for the production of decorative laminates was experimentally studied. The work involved: i) the industrial synthesis of traditional and modified resols with 10%w/w of sodium lignosulfonate and kraft-type lignin; ii) the industrial impregnation of kraft-type paper with the produced resins; iii) the production of laminates on both laboratory and industrial scales; and iv) the measurement of their final properties. The mechanical performance of the laminates was evaluated via the determination of the Young modulus, bending strength, biaxial impact strength, and Mode-I interlaminar fracture toughness. The (modified and traditional) laminates exhibited statistically significant differences in mechanical properties. However, the partial lignin replacement did not produce effects that were detrimental effects to the overall performance of the decorative laminates.